Individual Analysts' Stock Recommendations, Earnings Forecasts, and the Informativeness of Conference Call Question and Answer Sessions - Mayew, William J.; Sethuraman, Mani; Venkatachalam, Mohan (The Accounting Review, 2020)
ABSTRACT This paper deepens our understanding of the anatomy of an earnings conference call. Prior research indicates that, on average, analysts providing bullish stock recommendations or beatable earnings forecasts benefit from greater access to corporate management. Therefore, we analyze whether and to what extent individual analysts' ex ante stock recommendations and earnings forecasts affect the information content of analyst-manager conversations. Using intraday absolute stock price reactions around specific analyst-manager dialogs to measure informativeness, we find that manager dialogs with bearish analysts whose forecasts are missed are more informative. Such analysts engage in longer conversations with more back-and-forth iterations and exhibit a more negative tone, relative to bullish analysts that provide beatable forecasts. Stock prices directionally respond to both the analyst's linguistic tone and the manager's voice pitch. In sum, the capital market effects during an earnings conference call are far more nuanced than previously documented.